Модель подання знань на спеціалізованому Інтернет-порталі в області опору матеріалів - Globa, L. S.; Novogrudsca, R. L. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
The technology of building the specialized knowledge Internet-portal in the field of materials strength is presented here. The ontology that provides the equal knowledge and data representation and also their semantic connectivity is used for knowledge representation model on the portal. Using the concepts determined in the ontology the inner storages of portal are built, as well as information filling, navigation and search are organized.